Application of the Multi‐Process Action Control Framework to Understand Parental Support of Child and Youth Physical Activity, Sleep, and Screen Time Behaviours. Issue 2 (11th February 2019) - Rhodes, Ryan E.; Berry, Tanya; Faulkner, Guy; Latimer‐Cheung, Amy E.; O'Reilly, Norman; Tremblay, Mark S.; Vanderloo, Leigh; Spence, John C.
Abstract : Background: The purpose of this paper was to apply a framework designed to evaluate the intention–behaviour gap, known as multi‐process action control (M‐PAC), to understand parental support for the Canadian 24‐Hour Movement Guidelines for Children and Youth. Method: Parents ( N  =   1, 208) of children 5–17 years of age, completed measures of reflective (attitudes, perceived control), regulatory (planning), and reflexive (identity, habit) processes as well as intention and support behaviours. Results: Parents had significantly ( p  <   .01) higher intentions in descending order to support sleep (86%), reduce screen time (62%), or support physical activity (65% to 61%). Translation of these intentions into behaviour was also significantly ( p  <   .01) higher in a descending pattern for sleep support (80%), screen time reduction (68%), and physical activity support (56% to 31%). Congruent with M‐PAC, a discriminant function analysis of the results showed that the translation of parental support intentions into behaviour was associated with a combination of reflective, regulatory, and reflexive antecedents but these varied by the behaviours. Conclusion: The majority of parents have positive intentions to support child and youth health behaviours, yet many fail to enact this support. Translation of intention into action was associated with attitudinal aspects, control over support, self‐regulation skills, and parental habits and identity.